Evaluasi Pelaksanaan Pembelajaran Tematik di SD Islam Al-Khairiyah Jakarta Utara - Abdul Haq; Achmad Saprudin; Nida Nisrina; Rekha Pandini (SAP (Susunan Artikel Pendidikan), 2023)
The purpose of this study is to evaluate the implementation of thematic learning in the fourth grade of SD Islam Al-Khairiyah, North Jakarta. Since SD Islam Al-Khairiyah has implemented thematic learning, there has never been an evaluation of the implementation of thematic learning, so it is necessary to conduct research to obtain information and objective data related to components that affect the success of the implementation of thematic learning. This research is evaluative research with CIPP model. The subjects of this study were the Principal of Al-Khairiyah Islamic Elementary School and fourth grade Teachers. This evaluation research was carried out in 2022 with the sampling method was purposive sampling. Data collection was obtained through interviews, observation, and documentation. The steps of data analysis include the data reduction, data presentation, conclusion and verification. the data validity checking was using triangulation technique. The results of the research on aspects of thematic learning planning, aspects of teacher academic qualifications, aspects of educational infrastructure, aspects of thematic learning implementation, and aspects of learning assessment results indicated that the implementation of thematic learning applied at SDI Al-Khairiyah has been running well and  following the standard of the education process.